2021
DOI: 10.1121/10.0008899
|View full text |Cite
|
Sign up to set email alerts
|

Adults with cochlear implants can use prosody to determine the clausal structure of spoken sentences

Abstract: Speech prosody, including pitch contour, word stress, pauses, and vowel lengthening, can aid the detection of the clausal structure of a multi-clause sentence and this, in turn, can help listeners determine the meaning. However, for cochlear implant (CI) users, the reduced acoustic richness of the signal raises the question of whether CI users may have difficulty using sentence prosody to detect syntactic clause boundaries within sentences or whether this ability is rescued by the redundancy of the prosodic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 112 publications
1
3
0
Order By: Relevance
“…It has been shown that when hearing lists of digits for recall, pupil size progressively increases with the incremental arrival of list items, commonly interpreted as reflecting the build-up of the memory load prior to recall (Granholm et al, 1996; Kahneman & Beatty, 1966; Peavler, 1974). A similar progressive increase in pupil dilation has been shown over the course of hearing a sentence presented for recall (Amichetti et al, 2021; Piquado et al, 2010). As we have seen, however, this was not the case for the narrative passages.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It has been shown that when hearing lists of digits for recall, pupil size progressively increases with the incremental arrival of list items, commonly interpreted as reflecting the build-up of the memory load prior to recall (Granholm et al, 1996; Kahneman & Beatty, 1966; Peavler, 1974). A similar progressive increase in pupil dilation has been shown over the course of hearing a sentence presented for recall (Amichetti et al, 2021; Piquado et al, 2010). As we have seen, however, this was not the case for the narrative passages.…”
Section: Discussionsupporting
confidence: 69%
“…In this method, a speech processing algorithm periodically deletes small segments of speech and silent periods from the speech recording, abutting the remaining segments. The result is speech delivered in less than its original playing time, while leaving the original pitch (F0) unchanged, as well as maintaining the relative prosodic cues of inter- and intra-word timing patterns present in the original utterance that are important for speech understanding at the linguistic level, such as the relative lengthening of clause-final words and silent pauses that can signal that a clause boundary has been reached (Amichetti et al, 2021; Hoyte et al, 2009; Nooteboom, 1997; Shattuck-Hufnagel & Turk, 1996). Although time compression has a detrimental effect on comprehension and recall of speech by individuals with normal hearing, as might be expected, the effect is dramatically increased when combined with the degraded signal of a CI (Ji et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SP utterances (i.e., catchy sentences, sung speech, etc.) were found to enhance children’s working memory performance ( Yuzawa, 2002 ; Roy and Chiat, 2004 ; Yuzawa and Saito, 2006 ), promote speech production ( Adams and Gathercole, 1995 ; Baddeley, 2003 ), and facilitate speech acquisition ( Mehler et al, 1988 ; Leong et al, 2017 ; Amichetti et al, 2021 ). The findings in our study highlight the significance of catchy utterance materials in the speech development of children.…”
Section: Discussionmentioning
confidence: 99%
“…An objective measurement method that measures changes in the task-evoked pupil dilation. An increased pupil dilation is seen when the effort needed increases (35).…”
Section: Pupillometrymentioning
confidence: 98%